SMART HOME SYSTEM WITH RADIO FREQUENCY USING BLYNK APPLICATION - Rafif Okta Dwiansyah; Dedi Ary Prasetya (Emitor: Jurnal Teknik Elektro, 2022)
Over time, technology has been embedded in our daily lives and will develop more and more rapidly. Because everything can facilitate us in activities, especially in a house. But the problem arises how we manage and control electronic equipment efficiently and comfortably. In this study, an intelligent control system based on IoT (Internet of Things) technology has been suggested to solve the above problem, namely with a smart home control system based on IoT (Internet of Things) with a radio frequency of 433 MHz as a command to send and be forwarded to several receivers on each - each relay uses an IoT (Internet of Things) application, namely Blynk on a smartphone, it can also be controlled manually using a wireless button control and can be controlled remotely with a frequency of 433mhz. Through a series of control modules, such as switch modules, radio frequency control modules, you can directly control all kinds of household appliances. With smart phone can also communicate with smart center controller via wireless router via Wi-Fi interface. Because it has a radio frequency of 433 MHz as the bottom control layer, tools can be added to or removed from the control system very easily. And this control system functions as a switch that is connected to several receivers to each relay.